Students’ Interest in Participating the Extracurricular Public High School Basketball in Ilir Barat 1 District - Mulyaniarti, Gusti; Rahman, Andi; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
This study was to determine students’ interest in extracurricular activities of public high school basketball in Ilir Barat 1 sub-district. This research is qualitative descriptive research. This study uses a qualitative approach to obtain information about interest in participating in extracurricular basketball in students of SMA Negeri 1 Palembang, SMA Negeri 10 Palembang, and SMA Negeri 2 Palembang. This study uses a type of descriptive research, which is research that seeks to describe or explain the survey of extracurricular interest in basketball in students. The research was carried out using an instrument in the form of questionnaires of student interest in extracurricular basketball. The overall data that have been researched related to students’ interest in extracurricular basketball fit into the strong criteria. For the overall percentage at SMA Negeri 1 Palembang which is 75.84%, for the overall percentage at SMA Negeri 10 Palembang which is 63.20%, for the overall percentage at SMA Negeri 2 Palembang which is 69.12%. From the results of the data analysis, it was concluded that the strongest interest in participating in extracurricular basketball was SMA Negeri 1 Palembang, followed by SMA Negeri 2 Palembang, and finally SMA Negeri 10 Palembang. For the total overall results, students’ interest in participating in extracurricular public high school basketball in Ilir Barat 1 sub-district is 69.27% or can be categorized as strong interest.